IMPLEMENTING CRITICAL LITERACY TO REFRAME NARRATIVE STORIES: A CASE STUDY OF INDONESIAN TERTIARY EFL CLASSROOM - Hanif Nurcholish Adiantika; Emi Emilia; Gin Gin Gustine (Indonesian EFL Journal, 2025)
Critical literacy (CL) emphasizes the analysis of texts to understand power dynamics and promote social justice, helping students challenge established norms. However, further research is needed on its integration into the English curriculum for Indonesian university students. This case study explores the strategies used by an EFL teacher to foster CL development among 28 student-teachers at an Indonesian university through narrative texts. Data was gathered through classroom observations, students' reflective journals, and interviews, and thematically analyzed. Findings revealed that the teacher applied strategies such as "reader as code breaker," "reader as meaning maker," "reader as text user," and "reader as text analyst." Additionally, the Four Resources Model of CL enhanced students' abilities, particularly in meaning-making and text critique. Practical implications for curriculum design suggest that integrating CL strategies into the EFL curriculum can encourage students to engage more critically with texts, fostering deeper understanding and social awareness. For teacher training, this study highlights the importance of equipping educators with strategies for facilitating critical literacy in diverse classroom settings. The study advocates for a systematic integration of CL in EFL curricula across Indonesian higher education to enhance the quality of English programs and prepare students for more active participation in global discourse.